A novel art for binary pattern recognition - Matsunaga, G. (2002)
Adaptive resonance architectures are neural networks that self-organize stable pattern recognition codes in real-time in response to arbitrary sequence of input patterns. In this work we explore its drawbacks and propose several modi cations. Comparativesimulations show the better performance of our algorithm.